2022
DOI: 10.1039/d2na00427e
|View full text |Cite
|
Sign up to set email alerts
|

Superhigh energy storage density on-chip capacitors with ferroelectric Hf0.5Zr0.5O2/antiferroelectric Hf0.25Zr0.75O2 bilayer nanofilms fabricated by plasma-enhanced atomic layer deposition

Abstract: Thanks to excellent compatibility with complementary metal-oxide-semiconductor (CMOS) process, high permittivity HfO2/ZrO2-based thin films have emerged as potential candidates for high-performance on-chip energy storage capacitors of miniaturized energy-autonomous systems. However,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Regarding the sample without Al doping, the resulting peak is located at 30.8 • , corresponding to the T-(011) phase, and the position of the resulting peaks have no change, as the Al/(Hf + Zr) ratio rises from 1/40 to 1/32. When the Al/(Hf + Zr) ratio is 1/24, the resulting two peaks appear at 30.4 • and 30.17 Moreover, Table 1 compares our work with other HfO 2 -based AFE capacitors [5][6][7]9,10,13,14,21,22]. It is observed that our capacitor with the Al/(Hf + Zr) ratio of 1/16 demonstrates the highest ESD at 6 MV cm −1 together with a perfect ESE.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…Regarding the sample without Al doping, the resulting peak is located at 30.8 • , corresponding to the T-(011) phase, and the position of the resulting peaks have no change, as the Al/(Hf + Zr) ratio rises from 1/40 to 1/32. When the Al/(Hf + Zr) ratio is 1/24, the resulting two peaks appear at 30.4 • and 30.17 Moreover, Table 1 compares our work with other HfO 2 -based AFE capacitors [5][6][7]9,10,13,14,21,22]. It is observed that our capacitor with the Al/(Hf + Zr) ratio of 1/16 demonstrates the highest ESD at 6 MV cm −1 together with a perfect ESE.…”
Section: Resultsmentioning
confidence: 71%
“…Further, in combination with good reliability, excellent thermal stability and eco-friendly properties, the doped HfO 2 AFE dielectrics are considered to be very promising materials for on-chip energy storage applications [8]. To improve the ESD of capacitors, our recent studies indicate that the employment of a 1 nm Hf 0.5 Zr 0.5 O 2 underlying layer between the bottom electrode and the AFE Hf 0.25 Zr 0.75 O 2 layer can promote the generation of the AFE tetragonal (T)-phase in the AFE layer [9]. In addition, Yang et al reported a HfO 2 /ZrO 2 nanolaminate with a 2.2 nm HfO 2 thin film as the insertion layer between the TiN bottom electrode and ZrO 2 AFE thin film and achieved an ESD of up to 49.9 J cm −3 [10].…”
Section: Introductionmentioning
confidence: 99%
“…When the electric field is 3.03 MV/cm or less, the P–E curve behaves like a linear dielectric. This is because when the applied electric field is smaller than E T–O , strong polarization in the dielectric is unable to be generated. , As the maximum electric field increases from 3.03 to 6.21 MV/cm, P max increases quickly from 9.88 to 49.38 μC/cm 2 ; meanwhile, P r also increases from 0.22 to 16.12 μC/cm 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is challenging to achieve an ideal ESD and ESE simultaneously. Recently, nanoscale multilayer dielectrics based on AFE materials have been attempted for energy storage capacitor applications, such as Hf 0.5 Zr 0.5 O 2 (1 nm)/Hf 0.25 Zr 0.75 O 2 and TiO 2 (1 nm)/ZrO 2 /TiO 2 (1 nm), demonstrating good potential for enhancement of device performance. In a word, to obtain superior dielectric candidates for energy storage applications, it is indispensable to explore atomic layer doping of multiple components for AFE energy storage capacitors …”
Section: Introductionmentioning
confidence: 99%
“…Thus, it can protect the components from breakdown during the operating of the chip. 9,10 Based on the ECE and pyroelectricity, ferroelectric thin films can achieve efficient solid-state refrigeration and temperature change detection in the micro-region of the chips. 11–13 Therefore, a promising approach that has gained considerable attention is the utilization of ferroelectric thin films for chip-level power and thermal management.…”
Section: Introductionmentioning
confidence: 99%